PEMODELAN INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA DI PROVINSI PAPUA DAN PAPUA BARAT TAHUN 2014 - Vita Fibriyani; Ani Afifah (Universitas Bumigora, 2018)
Human Development Index is a measure of human development achievement based on the appropriate dimensions of health, education, and living. Papua is located in eastern Indonesia consisting of 2 provinces of Papua and west Papua. This study conducted a research about modeling of district/city of human development index value using binary logistic regression model, estimation of model parameters using maximum likelihood method. The data used in this study is secondary data obtained from the central statistical agencies of Papua and West Papua provinces. This study involved several factors that predicted to be affected the Human Development Index of district/city in both provinces, namely PDRB/capita, sex ratio, population density, population growth rate and number of mobile health centers. Based on the result of the analysis, it can be seen that the independent variables that significantly influence the value of Human Development Index of district/city in Papua 2014 is income/capita with the probability value of 0.003 and the population of mobile health centers with the probability of 0.034